Alkali-Wrapped Concrete Prism Test (AW-CPT) – New Testing Protocol Toward a Performance Test against Alkali-Silica Reaction - Ogawa, Shoichi; Kawabata, Yuichiro; Sagawa, Yasutaka; Yamada, Kazuo (Journal of Advanced Concrete Technology, 2018)
A new testing protocol, Alkali-Wrapped Concrete Prism Test (AW-CPT), is proposed to avoid alkali leaching and drying, which considerably influence expansion behavior of concrete affected by alkali-silica reaction (ASR). The approach used in this test is that a concrete specimen is wrapped by wet cloth containing alkali solution mimicking the alkalinity of the concrete pore solution. The proposed testing protocol was validated through laboratory and field-exposure measurements, with a focus on expansion, alkali mass balance, and mass change. The test results clearly showed that alkali leaching and drying were significantly reduced by using the AW-CPT method. AW-CPT gives a conservative threshold total alkali content, while conventional CPT overestimates it. The test results also highlighted that there may be an optimum condition of temperature and level of alkali boosting for each reactive aggregate.